Feed Rate Optimization for Five Axis Milling with an Iso-scallop Tool Path - Eranga, Ashan; Dissanayaka, Supun; Hamontree, Chaowalit (My University, 2022)
Five-axis milling tool path generation and feed rate optimization are challenging tasks. Our previous attempt provided a solution for an iso-scallop initial path determination using an optimal feeding direction (OFD) method that was efficient and maintained the quality of the machining surface. This paper extended the method with feed rate optimization to improve the machining time. Maximal allowable feed rate concept was used to define the objective function which was depended on A and B axis of the machine. To achieve smooth rotary axes motion, two B-splines were used to represent each axis. Then the non-linear optimization problem was solved using the interior-point algorithm with the constraint on global collision. Finally, the predetermined iso-scallop path was combined with the optimized tool orientation. The orientation optimization strategy was compared with constant lead angle and tool orientation smoothing method. Simulation results showed that our variable feed rate assignment decrease the machining time.
Keywords: B-spline; feed rate; flow curves; iso-scallop; OFD